2018
DOI: 10.6065/apem.2018.23.3.113
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics in Japanese children with nonobese type 2 diabetes

Abstract: It is well known that the incidence of youth-onset type 2 diabetes is increasing worldwide. On the other hand, most studies have shown that the majority of youth-onset type 2 diabetes occurs in obese individuals, generally with a body mass index (BMI) greater than the 90th or 95th centile for sex- and age-matched children and adolescents. However, we identified some Japanese children with nonobese type 2 diabetes and BMI less than 90th centile by a urine glucose screening program at schools in the Tokyo Metrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…It has been reported that the 14 association of obesity with glucose metabolism disorders is not as strong in children and adolescents as it Caucasian children and approximately 10%-15% of Japanese children with type2 diabetes exhibit normal weight with mild insulin resistance and substantial insulin secretion failure. [29,30] It is popularly thought that basic genetic defect of the β cell is required for the development of type 2 diabetes, and insulin resistance is merely an acquired stimulus. [31] In the face of severe peripheral insulin resistance, patients who cannot maintain adequate β-cell secretion, probably because of genetically determined factors, easily develop glucose metabolism disorders.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the 14 association of obesity with glucose metabolism disorders is not as strong in children and adolescents as it Caucasian children and approximately 10%-15% of Japanese children with type2 diabetes exhibit normal weight with mild insulin resistance and substantial insulin secretion failure. [29,30] It is popularly thought that basic genetic defect of the β cell is required for the development of type 2 diabetes, and insulin resistance is merely an acquired stimulus. [31] In the face of severe peripheral insulin resistance, patients who cannot maintain adequate β-cell secretion, probably because of genetically determined factors, easily develop glucose metabolism disorders.…”
Section: Discussionmentioning
confidence: 99%
“…In adults, it was reported that men have a higher tendency to accumulate VFA compared to pre-menopausal women [ 33 ]. In addition, it was reported that the Asian population is more susceptible to metabolic derangement induced by mild obesity than the Caucasian population [ 34 ]. There are few reports about the difference in VFA in children.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the SFA in the former was lower than that in the latter. Some non-obese Japanese children with type 2 diabetes mellitus have a large amount of visceral fat, even though their body weights and SFAs appear normal for their age and sex, while their V/S ratios are high 3…”
Section: Discussionmentioning
confidence: 99%
“…Abdominal obesity is highly associated with metabolic risk factors, even in childhood 1. Furthermore, the incidence rate of youth-onset type 2 diabetes mellitus is increasing worldwide,2,3 and the Asian population is reportedly more susceptible to metabolic derangement induced by mild obesity than is the Caucasian population 3. Even though the average body mass index (BMI) of Asians is lower than that of Caucasians, the prevalence of type 2 diabetes mellitus is higher in Asians, possibly owing to the greater accumulation of visceral adiposity other than subcutaneous fat 4.…”
Section: Introductionmentioning
confidence: 99%